Attrition with spinal cord stimulation. (2nd November 2015) - Mann, Stacey A.; Sparkes, Elizabeth; Duarte, Rui V.; Raphael, Jon H.
Abstract : The aim of this prospective study was to investigate whether spinal cord stimulation (SCS) significantly reduces pain intensity for up to 18-month follow-up in patients with chronic neuropathic pain. Forty-eight patients were recruited. Patients rated their pain using a Visual analog scale (VAS) and pain-related disability using the Oswestry Disability Index (ODI) at baseline (1 week prior to SCS surgery) and at 6-, 12-, and 18-month follow-up. Pain intensity significantly decreased from baseline to all 3 time points [F (3, 135) = 16.264, p < 0.001]. The greatest difference in the reduction of pain intensity was observed between baseline (M = 7.20, SD = 1.34) and 6-month follow-up (M = 4.60, SD = 2.20), [t(47) = 6.741, p < 0.001]. However, when looking at differences between the 6-month follow-up and subsequent assessments, statistically significant increases in pain intensity from the 6-month to the 12-month follow-up [t(47) = −2.788, p = 0.008], and from the 6-month to the 18-month follow-up [t(47) = −3.339, p = 0.002] could be observed. Statistically significant changes were also observed for clinical changes in pain scores [F (2, 94) = 4.972, p = 0.009. There was a significant decrease in the percentage of clinical change obtained from the 6-month (M = 33.19, SD = 35.63) to the 12-month follow-up (M = 23.76, SD = 33.62), [t(47) = 2.347, p = 0.025], and from the 6-month to the 18-month follow-up (M = 18.34, SD = 33.51), [t(47) = 3.072, p = 0.004]. A number of patients also reported higher levels of pain intensity at the 12-and 18-month follow-up than at baseline. Pain-related disability scores significantly decreased from baseline (M = 55.04, SD = 16.43) to the 6-month follow up (M = 46.98, SD = 19.05), [t(47) = 3.464, p = 0.001] and from baseline to the 12-month follow up (M = 48.49, SD = 20.94), [t(47) = 2.918, p = 0.005], but not during the 18-month follow up (M = 51.75, SD = 20.92), [t(47) = 1.330, p = .190]. There was a significant increase in pain-related disability between the 6- and the 18-month follow up [t(47) = −2.188. p = 0.034]. These findings suggest that the beneficial effect of SCS on pain intensity may diminish over time, and that the 6-month follow-up scores may reflect a placebo effect.